2004
DOI: 10.1007/s00415-004-0541-x
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant nocturnal frontal lobe epilepsy

Abstract: Autosomal dominant nocturnal frontal lobe epilepsy (ADNFLE) is an idiopathic epilepsy, with a spectrum of clinical manifestations, ranging from brief, stereotyped, sudden arousals to more complex dystonic-dyskinetic seizures. Video-polysomnography allows a correct differential diagnosis. There is no difference between sporadic nocturnal frontal lobe epilepsy (NFLE) and ADNFLE in the clinical and neurophysiological findings. ADNFLE is the first idiopathic epilepsy for which a genetic basis has been identified. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
93
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(95 citation statements)
references
References 106 publications
2
93
0
Order By: Relevance
“…(1) ADNFLE seizures are typically characterized by repetitive jerky limb movements and asymmetrical posturing (for review, see Combi et al, 2004). Nicotine seizures in L9ЈA mice consist of forelimb clonus and loss of righting response (which can also be described as asymmetrical posturing).…”
Section: Similarities With Adnflementioning
confidence: 99%
See 1 more Smart Citation
“…(1) ADNFLE seizures are typically characterized by repetitive jerky limb movements and asymmetrical posturing (for review, see Combi et al, 2004). Nicotine seizures in L9ЈA mice consist of forelimb clonus and loss of righting response (which can also be described as asymmetrical posturing).…”
Section: Similarities With Adnflementioning
confidence: 99%
“…parallel between ADNFLE and nicotine seizures in L9ЈA mice is that ϳ70% of ADNFLE patients have nondiagnostic EEGs Oldani et al, 1998;Rozycka et al, 2003) (for review, see Combi et al, 2004). Nicotine seizures in L9ЈA were undetected by EEG.…”
Section: Similarities With Adnflementioning
confidence: 99%
“…In particular, S284L was also identified in the sporadic form NFLE (Phillips et al, 2000). All ADNFLE/ NFLE mutations were heterozygous and within the nAChR gating regulator or pore region (Wonnacott, 1997;Combi et al, 2004;Bertrand et al, 2005), and dysfunctions of the corresponding channel have been demonstrated in vitro.…”
Section: Introductionmentioning
confidence: 98%
“…Numerous variations in Cys-loop ligandgated ion channels have been shown to be causative of channelopathies (18,19). A single-nucleotide polymorphism in the human HTR3B gene giving rise to the nonsynonymous variation Y129S in the 5-HT 3B subunit has been identified in very high frequencies in worldwide populations.…”
mentioning
confidence: 99%